The impact of trade and technology on wage components - Linda Borrs; Florian Knauth (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
We use a large sample of German workers to analyze the effect of low-wage competition with China and Eastern Europe (the East) on the wage structure within German manufacturing industries. Utilizing the method by Abowd et al. (1999), we decompose wages into firm and worker components. We find that the rise of market access and competitiveness of the East has a substantial impact on the dispersion of the worker wage component and in part on positive assortative matching. Trade fails to explain changes in the firm wage premium. The rising dispersion in worker-specific wages can be attributed to increasing skill premia and to changes in the extensive margin of the workforce, leading to a wage polarization for the remaining within-industry workers. We also account for technological change by considering how many routine-intensive jobs are substituted within an industry. The more routine jobs are cut, the higher is the effect on wage inequality, especially on the dispersion of worker-specific wages. Overall, trade explains up to 19% of the recent increase in wage inequality and slightly exceeds the technology effect that accounts for approximately 17%.
Keywords: F16; J31; O33; F14; 330; wage decomposition; wage inequality; globalization; gravity